The role of academic libraries in implementing research data services: a case study of the University of KwaZulu-Natal Libraries - Madibi, Zizipho (Department of Knowledge and Information Stewardship, 2022)
This study investigated the role of academic libraries in implementing research data services, UKZN being the case study. The objectives of the study were to identify the need for research data services among UKZN researchers, to identify the major challenges associated with introducing research data services at UKZN, and to determine the possibility of implementing research data services at UKZN Libraries. The Data Curation Centre Lifecycle model was adopted as a framework for the study as it manages to connect the different stages of research data management. The study took a mixed methods approach of which interviews and a survey were used. A purposive sample was used to select library staff and random sample was drawn from 1341 UKZN academics. From a sample of 1341, 299 was the minimum size recommended by the Raosoft sample size calculator for a 5% margin of error and 95% confidence level. For quantitative analysis, an online questionnaire was administered using Google Forms. A series of questions were formulated for guidance in obtaining answers to the study objectives. Google Forms was used for the analysis while figures and tables were created using Microsoft Excel. Interviews from the library staff were recorded and data from interviews was transcribed into Microsoft Word. The study revealed that UKZN Libraries are still struggling with RDM policy development. The findings of the study revealed that researchers who responded to the study showed a lack of RDM awareness while library staff showed a moderate level of awareness. The study revealed that researchers at UKZN work with different types of data and they use different storage options such as removable storage devices, computer hard drives and cloud services. Although a few researchers have developed data management plans at UKZN, they have not done so because they were mandated by the institution - UKZN has not yet developed DMPs and library staff are not aware which funders require DMPs. The researchers who responded to the study showed interest in different trainings such as, training on data storage, development of DMPs and metadata creation. The library staff were more eager to provide data storage, data archiving and sharing mainly because of the existence of the UKZN data repository (Yabelana). Study recommendations are based on the analysed data. One of the recommendations was that UKZN Libraries should assume a role of being an advisor and trainer for research data services at UKZN.